Treatment of autosomal dominant hearing loss by in vivo delivery of genome editing agents - Gao, Xue; Tao, Yong; Lamas, Veronica; Huang, Mingqian; Yeh, Wei-Hsi; Pan, Bifeng; Hu, Yu-Juan; Hu, Johnny H.; Thompson, David B.; Shu, Yilai; Li, Yamin; Wang, Hongyang; et al. (Nature (London), 2018)
CRISPR–Cas9 genome editing is used to correct a dominant-negative mutation in a mouse model of inherited deafness, resulting in improvements in cochlear function and hearing. Hindering heritable hearing loss Nearly half of all deafness cases arise from genetic factors, yet there are limited treatment options available for inherited hearing loss. David Liu and colleagues develop a genome-editing approach to target a dominantly inherited form of deafness. In a mouse model of human deafness, CRISPR–Cas9 editing can disrupt the mutant allele and reduce hearing loss. The results support the potential utility of protein–RNA complex delivery in post-mitotic cells as a gene-editing strategy for some autosomal-dominant diseases. Although genetic factors contribute to almost half of all cases of deafness, treatment options for genetic deafness are limited 1 , 2 , 3 , 4 , 5 . We developed a genome-editing approach to target a dominantly inherited form of genetic deafness. Here we show that cationic lipid-mediated in vivo delivery of Cas9–guide RNA complexes can ameliorate hearing loss in a mouse model of human genetic deafness. We designed and validated, both in vitro and in primary fibroblasts, genome editing agents that preferentially disrupt the dominant deafness-associated allele in the Tmc1 (transmembrane channel-like gene family 1) Beethoven ( Bth ) mouse model, even though the mutant Tmc1 Bth allele differs from the wild-type allele at only a single base pair. Injection of Cas9–guide RNA–lipid complexes targeting the Tmc1 Bth allele into the cochlea of neonatal Tmc1 Bth /+ mice substantially reduced progressive hearing loss. We observed higher hair cell survival rates and lower auditory brainstem response thresholds in injected ears than in uninjected ears or ears injected with control complexes that targeted an unrelated gene. Enhanced acoustic startle responses were observed among injected compared to uninjected Tmc1 Bth /+ mice. These findings suggest that protein–RNA complex delivery of target gene-disrupting agents in vivo is a potential strategy for the treatment of some types of autosomal-dominant hearing loss.